Analysis Of Factors That Influence K Content Escherichia Coli Bacteria In Dairy Cow Milk In Bendungan District Trenggalek Regency - Risqa Lutfia Nirmala; Amarin Yudhana (Universitas STRADA Indonesia, 2020)
Milk quality is determined by bacteria contained in milk because bacteria can damage and change the chemical, physical and organoleptic properties of milk. Unhygienic milking process can cause bacterial contamination. Purpose: To determine the factors that influence the presence of Escherichia coli in fresh cow's milk. in Bendungan sub-district. Method: The research design is quantitative with a cross-sectional approach. The population is 32, data collection techniques with laboratory examinations and observations with sampling techniques using Cluster sampling . This study was conducted from February to March 2020. Data collection using questionnaires. Data is processed using the SPSS program with the Logistic Regression test . Results: personal hygiene (43.8% ) is not good , there is a significant influence of personal hygiene on the content of Eschericia Coli ( Ρ Value 0.043), equipment hygiene (37.5%) is not good, there is an influence of equipment hygiene on the content of Eschericia Coli ( Ρ Value 0.045 ) , cage sanitation (50.0% ) is not good, there is a significant influence of cage sanitation on the content of Eschericia Coli ( Ρ Value 0.048) , cow cleanliness 53.1% , not good, there is a significant influence of cow cleanliness on Eschericia Coli content ( Ρ Value 0.039) and for the content of Eschericia Coli included in the category of not meeting health requirements, namely 21 respondents (66%) of the total 32 respondents . All variables have a significant effect on the content of Eschericia Coli. This is caused by the improper milking process and bacteria can move from one object to another. Conclusion : personal hygiene, equipment hygiene, barn sanitation, and cow cleanliness can affect the content of Eschericia Coli in cow's milk. It is recommended that the Animal Husbandry Service increase milking supervision to ensure the quality of cow's milk .